HDAC6 regulates human erythroid differentiation through modulation of JAK2 signalling. Issue 2 (28th December 2022) - Vong, Pascal; Messaoudi, Kahia; Jankovsky, Nicolas; Gomilla, Cathy; Demont, Yohann; Caulier, Alexis; Jedraszak, Guillaume; Demagny, Julien; Djordjevic, Stefan; Boyer, Thomas; Marolleau, Jean Pierre; Rochette, Jacques; et al.
Abstract: Among histone deacetylases, HDAC6 is unusual in its cytoplasmic localization. Its inhibition leads to hyperacetylation of non‐histone proteins, inhibiting cell cycle, proliferation and apoptosis. Ricolinostat (ACY‐1215) is a selective inhibitor of the histone deacetylase HDAC6 with proven efficacy in the treatment of malignant diseases, but anaemia is one of the most frequent side effects. We investigated here the underlying mechanisms of this erythroid toxicity. We first confirmed that HDAC6 was strongly expressed at both RNA and protein levels in CD34 + ‐cells‐derived erythroid progenitors. ACY‐1215 exposure on CD34 + ‐cells driven in vitro towards the erythroid lineage led to a decreased cell count, an increased apoptotic rate and a delayed erythroid differentiation with accumulation of weakly hemoglobinized immature erythroblasts. This was accompanied by drastic changes in the transcriptomic profile of primary cells as shown by RNAseq. In erythroid cells, ACY‐1215 and shRNA‐mediated HDAC6 knockdown inhibited the EPO‐dependent JAK2 phosphorylation. Using acetylome, we identified 14‐3‐3ζ, known to interact directly with the JAK2 negative regulator LNK, as a potential HDAC6 target in erythroid cells. We confirmed that 14‐3‐3ζ was hyperacetylated after ACY‐1215 exposure, which decreased the 14‐3‐3ζ/LNK interaction while increased LNK ability to interact with JAK2. Thus, in addition to its previously described role in the enucleation of mouse fetal liver erythroblasts, we identified here a new mechanism of HDAC6‐dependent control of erythropoiesis through 14‐3‐3ζ acetylation level, LNK availability and finally JAK2 activation in response to EPO, which is crucial downstream of EPO‐R activation for human erythroid cell survival, proliferation and differentiation.